Element mobility related to rock weathering and soil formation at the westward side of the southernmost Patagonian Andes - Klaes, Bjorn; Woerner, Gerhard; Thiele-Bruhn, Soren; Arz, Helge Wolfgang; Struck, Julian; Dellwig, Olaf; Groschopf, Nora; Lorenz, Marcel; Wagner, Jean-Frank; Urrea, Oscar Baeza; Lamy, Frank; Kilian, Rolf (My University, 2022)
Rock weathering and pedogenesis are fundamental processes for elementmobility in terrestrial bio-geochemical cycles and for the regulation of primary productivity in adjacent coastal marine ecosystems. Here, soils developed from volcanic ash under extreme climate conditions could play a particular role. We therefore investigated rock weathering, soil formation and the associatedmobilization of trace elements andmicronutrients in a pristine South Patagonian ecosystem. Weathered and unweathered basement lithologies, tephra of the 4.216 kyrs BP Mt. Burney eruption and four soil profiles are considered. The approach combines mineralogical (XRD, SEM) and inorganic geochemical (XRF, ICPOES/MS) with organic geochemical analyses (TOC, TN, delta C-13, delta N-15, DOC extracts) of representative samples. Chemical weathering is quantified by mass balance calculations and C-14 age constraints allow a correlation of pedogenic processes with the paleoenvironmental history of the area. Our data document that pedogenesis with initial peat formation occurred since similar to 2.5 kyrs BP. In these acidic peaty Andosols, intensive alteration of volcanic glass mobilized large quantities of elements, considerably surpassing leachates provided by basement rock weathering. Clay production is limited in favor of the formation of amorphous Al- and crystalline Fe-(hydr)oxides. However, tephra alteration, soil organicmatter turnover rates, enhanced dissolved organic carbon export, and Fe-/Al-(hydr)oxide precipitation are closely linked and ultimately controlled by rainfall-induced water-level fluctuations, highlighting the dominant influence of the southern westerly wind belt. The transport of mobilized trace elements and micronutrients adsorbed onto suspended colloids (dissolved organic carbon, Al-humus complexes and Fe-(hydr)oxides) is redox-pH-dependent, highly variable and ultimately regulated by westerly intensity. Broader implications of this work include a new perspective on the climate-controlled micronutrient delivery for primary productivity in South Patagonian fjords, which is strongly affected by Andosol formation. Furthermore, a careful evaluation of 'ordinary' geochemical proxies in regional paleoenvironmental archives is needed to account for these unique pedogenic processes.
Keywords: tephra; volcanic glass; peat; andosol; micronutrients